Family Values: Decoding Boris Vian's Les Bâtisseurs d'empire - Laurence M. Porter (Studies in 20th & 21st Century Literature, 1997)
Although the full intricacy of his accomplishment has not yet been recognized, Vian interweaves three codes in this play: the absurdist, the anti-colonial, and the psychoanalytical. A bourgeois family periodically retreats from a terrifying noise, moving upstairs into a series of ever-smaller apartments. In each they find already established the "schmürz"—a battered, silent scapegoat figure—and at each new level they lose a member of the family, until finally only le Père and the schmürz remain. Presumably they perish at the end. In 1959, the shrinking space suggested the shrinking French overseas empire, and the schmürz, its colonized victims. The disintegrating family figures the fragmentation of the individual into dissociated super ego, and id, incapable of mutual communication, a drama ending in a psychotic break. The absurdist features of repetition and non sequitur cannot totally conceal an underlying dramatic structure and the gradual emergence of the anti-colonialist, bourgeois critique code. The patriarchy cannot triumph without destroying itself. Its absolute reign entails total alienation. But Vian's denouement, a leurre, preserves absurdist indeterminacy.
Keywords: Boris Vian; Les Bâtisseurs d' empire; play; anti-colonial; colonialism; absurdist; theatre of the absurd; psychoanalytics; bourgeois; a leurre; family